2022
DOI: 10.1017/s0143814x22000241
|View full text |Cite
|
Sign up to set email alerts
|

Pollution and the public: how information accessibility conditions the public’s responsiveness to policy and outcomes

Abstract: This article advances a theory that brings real-world outcomes into our current understanding of the dynamic relationship between public opinion and policy. It examines a vital public good – air pollution remediation in 319 American localities – and estimates a dynamic model of relationships among three key variables: public opinion, policy, and air pollution outcomes. The analysis focuses on both public opinion and air pollution outcomes as dependent variables. I find that public opinion reacts to changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Studies in democratic political systems have shown that policy change has a robust statistical effect on the public's preferences in salient issue domains (Jennings 2009; Wlezien 1995), which reflects the public using reasonably accurate information about policy itself. The public also updates its opinions with outcomes information that is easy to obtain and interpret (Ansolabehere, Meredith, and Snowberg 2014; Buchanan 2022; Egan and Mullin 2012).…”
mentioning
confidence: 99%
“…Studies in democratic political systems have shown that policy change has a robust statistical effect on the public's preferences in salient issue domains (Jennings 2009; Wlezien 1995), which reflects the public using reasonably accurate information about policy itself. The public also updates its opinions with outcomes information that is easy to obtain and interpret (Ansolabehere, Meredith, and Snowberg 2014; Buchanan 2022; Egan and Mullin 2012).…”
mentioning
confidence: 99%